Penerapan manajemen risiko pada perbankan syariah berdasarkan regulasi Otoritas Jasa Keuangan (OJK) - Priyambodo, Alvin Dwi (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of risk management in Islamic banking based on regulations established by the Financial Services Authority (OJK). The method used in this study is a qualitative approach with a literature review, sourced from national journals and academic repositories. The results show that risk management in Islamic banks involves several stages, such as recognizing, calculating, monitoring, and controlling risks. Managed risks include financing risk, operational risk, market risk, liquidity risk, reputation risk, and risks related to compliance with Islamic principles. Good risk management implementation helps maintain financial health, improve bank performance, and strengthen customer trust. OJK regulations serve as the primary basis for ensuring the implementation of appropriate principles, through management oversight, adequate policies, and an effective internal control system. However, the implementation of risk management still faces several challenges, such as a lack of human resources, difficulty understanding complex products, and advances in digital technology that introduce new risks. Therefore, it is necessary to improve governance management, enhance human resource capabilities, and utilize information technology to support more effective risk management in Islamic banks.